Distress in hospitalized cancer patients: Associations with personality traits, clinical and psychosocial characteristics. Issue 5 (11th December 2021) - Pichler, Theresia; Marten‐Mittag, Birgitt; Hermelink, Kerstin; Telzerow, Eva; Frank, Tamara; Ackermann, Ulrike; Belka, Claus; Combs, Stephanie E.; Gratzke, Christian; Gschwend, Jürgen; Harbeck, Nadia; Heinemann, Volker; et al.
Abstract: Objective: To improve allocation of psychosocial care and to provide patient‐oriented support offers, identification of determinants of elevated distress is needed. So far, there is a lack of evidence investigating the interplay between individual disposition and current clinical and psychosocial determinants of distress in the inpatient setting. Methods: In this cross‐sectional study, we investigated 879 inpatients with different cancer sites treated in a German Comprehensive Cancer Center. Assessment of determinants of elevated distress included sociodemographic, clinical and psychosocial characteristics as well as dimensions of personality. Multiple linear regression was applied to identify determinants of psychosocial distress. Results: Mean age of the patients was M  = 61.9 (SD = 11.8), 48.1% were women. In the multiple linear regression model younger age ( β  = −0.061, p  = 0.033), higher neuroticism ( β  = 0.178, p  = <0.001), having metastases ( β  = 0.091, p  = 0.002), being in a worse physical condition ( β  = 0.380, p  = <0.001), depressive symptoms ( β  = 0.270, p  = <0.001), not feeling well informed about psychological support ( β  = 0.054, p  = 0.046) and previous uptake of psychological treatment ( β  = 0.067, p  = 0.020) showed significant associations with higher psychosocial distress. The adjusted R 2 of the overall model was 0.464. Conclusion: Controlling for sociodemographic characteristics and dispositional vulnerability, that is neuroticism, current clinical and psychosocial characteristics were still associated with hospitalized patients' psychosocial distress. Psycho‐oncologists should address both, the more transient emotional responses, such as depressive symptoms, as well as more enduring patient characteristics, like neuroticism.